The role of user experience towards customer loyalty with mediating role of customer satisfaction at Shopee - Upayana Wiguna Saputra (Review of Management, Accounting, and Business Studies, 2021)
Based on data from Badan Pusat Statistika Provinsi Bali (2020) shows that there was an increase of 23.49% in online shopping activities during Covid-19 pandemic in Bali Province. However, the satisfaction and loyalty of Shopee users decreased in the first quarter of 2021. This can be seen from the many bad reviews from reviews on Google Play Store and App Store related to the use of applications that often an error. This study aims to determine the loyalty of Shopee users, where customer satisfaction is the determinant of the perceptions generated by users' experience. With both positive and negative results from users, it will make Shopee users make satisfy to repeat purchases, and eventually become loyal customers. This study used 155 respondents tested using the PLS-SEM as a data analysis method. The result found that user experience has no significant effect on customer loyalty. User experience has a positive and significant effect on customer satisfaction. Customer satisfaction has a positive and significant effect on customer loyalty and also a partial mediation between user experience and customer loyalty. This study focused on the relationship between user experience, customer satisfaction, and loyalty.